Peran Innovation dalam Memoderasi Pengaruh Digital Marketing Content terhadap Marketing Performance Gula Nipah Sabuai - Dzikri Ramadhan; Ibnu Khajar (Yayasan Jompa Research and Development, 2026)
This study aims to analyze the effect of Digital Marketing Content on Marketing Performance and examine the moderating role of Innovation in the MSME product of Gula Nipah Sabuai. This research employed a quantitative explanatory approach using purposive sampling techniques involving 100 consumers of Gula Nipah Sabuai in Pangkalan Bun, Central Kalimantan. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).The findings reveal that Digital Marketing Content has a positive and significant effect on Marketing Performance. Innovation also has a positive direct effect on Marketing Performance. However, Innovation negatively moderates the relationship between Digital Marketing Content and Marketing Performance, indicating that innovation practices that are not aligned with digital content strategies may reduce marketing effectiveness. The model explains 54.1% of the variance in Marketing Performance.This study implies that MSMEs need to align product innovation with digital marketing strategies to improve marketing performance sustainably, particularly for local wisdom-based products.